Peningkatan Kesadaran Hukum Staf Perpustakaan UIN Gusdur terhadap Undang-Undang Perpustakaan Melalui In House Training - Prayogi, Arditya; Kamalludin, Iqbal; Pratami, Bunga Desyana (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
Legal awareness of a rule is important to have because with it a person will be able to carry out their professional duties and roles well in society. Thus, this community service activity took the form of an effort to increase legal awareness aimed at library staff at UIN Gusdur Pekalongan. The legal awareness that wants to be increased in this case is legal understanding of Law no. 43 of 2007 which regulates libraries. The main objective of this service activity is so that the activity participants have legal awareness of the library law. The method used in this service activity took the form of exposure-socialization using the format of in-house training (IHT). The result of this service activity is increased legal awareness and legal commitment for library staff to be able to carry out their professional duties in providing library services well